CONGENITAL HEART DISEASES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Congenital heart diseases (CHDs) represent the most common group of congenital anomalies worldwide, encompassing a diverse spectrum of structural and functional abnormalities arising from disruptions in cardiac embryogenesis. These conditions range from simple lesions with minimal physiological impact to complex malformations requiring lifelong medical and surgical management. This narrative review explores the developmental biology underlying cardiac formation, the genetic and environmental factors contributing to CHDs, and the pathophysiological mechanisms that drive clinical manifestations. We further examine advances in diagnostic modalities, including prenatal imaging and molecular screening, alongside evolving therapeutic approaches such as surgical correction, catheter-based interventions, and regenerative strategies. Understanding the multifactorial nature of CHDs is essential for improving early detection, optimizing patient outcomes, and advancing personalized cardiovascular care.